2022
DOI: 10.3389/fpubh.2022.977221
|View full text |Cite
|
Sign up to set email alerts
|

Management of capital liquidity in public hospitals under the epidemic situation of COVID-19

Abstract: The epidemic of COVID-19 has a great impact on the life and safety of people around the world. As the main force in the fight against COVID-19, the financial management of public hospitals will provide a strong guarantee for the diagnosis and treatment behavior of medical staff. The financial department needs to recognize the extent of the impact of COVID-19 on hospital finance, quantify and predict the potential risk factors, and develop reasonable financial management strategies. As an important part of asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Our findings also showed that liquidity ratios (cash ratio, current ratio, and quick ratio) experienced a decline during the pandemic. Poor capital liquidity affects the decision-making ability of public hospitals [ 53 ]. Public hospitals should ensure adequate capital liquidity to cope with the supplier’s accounts without any payment delay and have the ability to pay the medical staff [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also showed that liquidity ratios (cash ratio, current ratio, and quick ratio) experienced a decline during the pandemic. Poor capital liquidity affects the decision-making ability of public hospitals [ 53 ]. Public hospitals should ensure adequate capital liquidity to cope with the supplier’s accounts without any payment delay and have the ability to pay the medical staff [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor capital liquidity affects the decision-making ability of public hospitals [ 53 ]. Public hospitals should ensure adequate capital liquidity to cope with the supplier’s accounts without any payment delay and have the ability to pay the medical staff [ 53 ]. COVID-19 impacted not only health systems but also other sections of countries worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In the management of medical specialist department services, there is a role for the medical committee in determining clinical authority (Goldberg et al , 2013). The Medical Specialist Department has a different flow of consumption, budget and staff ownership depending on the complexity of medical care (Aarthy et al , 2021; Hu et al , 2022). Medical specialist department services are coordinated with external services such as ER, laboratory, radiology, maternity room and inpatient installation (Campbell et al , 2022).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Improving health services focuses on strengthening hospital service business processes. Efforts to improve service quality based on improving the hospital service value chain are also important, including listening to patient voices in service improvement initiatives (Hu et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Both lower and high-income countries, irrespective of the degree of the COVID-19 outbreak, reported a reduction in healthcare services utilization (Dopfer et al, 2020;Melnick and Maerki, 2021;Roy et al, 2021;He et al, 2022), especially in the early days of the pandemic (Coughlin et al, 2020;Xu et al, 2021;Kim et al, 2022). Studies indicate a general decrease in the bed occupancy rate (Hu et al, 2022), except for intensive care beds (Trentini et al, 2022).…”
Section: Hospitals Vs Pandemicmentioning
confidence: 99%